In-situ characterization method of graphite electrode microstructure stress in electrochemical process
By using spectral synthesis technology and DFT calculation, in-situ characterization of microstructure stress during electrochemical processes was achieved, solving the problem of difficulty in measuring stress distribution in electrode materials during electrochemical processes and improving the structural stability and lifespan of electrode materials.
Patent Information
- Application Number
- CN202511613503.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-01-27
AI Technical Summary
Existing technologies make it difficult to directly characterize the distribution and evolution of stress in electrode microstructures during electrochemical processes, which affects the structural stability and cycle life of electrode materials.
In-situ measurement of three-dimensional strain of microstructures was performed using spectroscopic synthesis techniques. Combined with DFT calculation of modulus evolution of typical lithium intercalation structures, an electrochemically induced stress characterization model based on microstructure strain and modulus was established. Strain was measured by Raman spectroscopy and XRD, and elastic coefficients were calculated by DFT to achieve in-situ characterization of microstructure stress.
Three-dimensional characterization of microstructure stress during electrochemical processes was achieved, revealing the electrochemical-mechanical coupling mechanism, optimizing electrode structure design, and improving the safety and durability of energy storage devices.
Smart Images

Figure CN121409485A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery new energy, specifically involving an in-situ characterization method for the stress of graphite electrode microstructure during electrochemical processes. Background Technology
[0002] Electrochemical energy storage primarily relies on the insertion and extraction of ions between the positive and negative electrodes to achieve charging and discharging. During this process, the lattice spacing and overall microstructure of the electrode active materials undergo reversible or irreversible volume expansion and contraction with changes in ion concentration. Taking graphite electrodes as an example, different stages of interlayer compounds are formed during lithium-ion insertion, leading to significant anisotropic strain distribution and phase boundary migration. These volume changes generate complex mechanical stress fields both within and between particles.
[0003] The accumulation and release of internal stress in electrode materials directly affect the structural stability and cycle life of energy storage devices. Excessive stress can lead to cracking, pulverization, and detachment of active particles, expansion or delamination of the electrode as a whole, and even cause problems such as diaphragm deformation under pressure and current collector peeling, ultimately resulting in capacity decay, increased internal resistance, and in severe cases, internal short circuits and thermal runaway. Therefore, a deep understanding and quantitative characterization of the evolution of electrode microstructure stress during electrochemical processes is of great significance for optimizing electrode material structure, improving performance, and predicting lifetime.
[0004] Currently, research on the micromechanical behavior of electrodes during electrochemical processes mainly focuses on strain measurement. Existing studies have utilized techniques such as in-situ X-ray diffraction (XRD), Raman spectroscopy, electron microscopy, and digital speckle correlation to obtain information on electrode deformation, phase transitions, and crack evolution at different scales. However, these methods largely remain at the strain level, making it difficult to directly obtain stress distribution and its evolution. The formation and evolution of electrochemically induced stress involve multiple aspects, including microstructural strain caused by ion concentration, the nonlinear effect of material modulus changes with concentration, microstructural anisotropy, and mechanical constitutive relations. How to achieve in-situ three-dimensional characterization of microstructural stress during electrochemical processes and establish a mechanical constitutive model based on the concentration dependence of material elastic modulus is a key scientific and technological problem that urgently needs to be solved in the field of electrode mechanics research. Developing a microstructural stress characterization method synchronized with the electrochemical process is of great significance for revealing the electrochemical-mechanical coupling mechanism, optimizing electrode structure design, and improving the safety and durability of energy storage devices. Summary of the Invention
[0005] This invention is proposed to address the problems existing in the prior art, and its purpose is to provide an in-situ characterization method for the stress of the microstructure of graphite electrodes during electrochemical processes.
[0006] The technical solution of this invention is: an in-situ characterization method for the microstructure stress of graphite electrodes during electrochemical processes, characterized by comprising the following steps: A. In-situ measurement of three-dimensional strain evolution information of microstructures using spectral synthesis technology; B. The modulus evolution of typical lithium intercalation structures was calculated using DFT; C. Establish an electrochemically induced stress characterization model based on microstructure strain and modulus.
[0007] Furthermore, step A includes in-situ experiments on the three-dimensional deformation of microstructures based on graphite electrodes, the specific process of which is as follows: First, composite electrodes are prepared using graphite materials; Then, the battery was assembled in a vacuum glove box using a graphite composite electrode as the positive electrode, lithium metal as the negative electrode, and a 25µm thick microporous polypropylene membrane as the separator. Finally, to achieve in-situ measurement of deformation, a CR2032 button cell with a transparent window and a PI film was used for in-situ observation and signal acquisition of the electrochemical process.
[0008] Furthermore, the spectral synthesis technique in step A involves the following specific steps: First, Raman spectroscopy was used to measure the in-plane strain of the microstructure. Then, XRD was used to measure the interlayer strain of the microstructure.
[0009] Furthermore, XRD was used to measure the interlayer strain of the microstructure, as follows: First, XRD instruments were used to collect spectral information in real time during the electrochemical process. By tracking the changes in the diffraction angle of the graphite diffraction peaks, the interlayer spacing parameters of the graphite lattice structure during the electrochemical process were given by Bragg's law. Then, based on the obtained interlayer spacing parameters, the specific expression of the micro-interlayer strain information of graphite is further calculated.
[0010] Furthermore, Raman spectroscopy was used to measure the in-plane strain of the microstructure. The specific process is as follows: Raman spectroscopy was used to collect spectral information in real time during the electrochemical process, and the specific expression of strain information in the graphite microstructure was obtained by tracking the changes in 2D peak positions.
[0011] Furthermore, step B uses DFT to calculate the modulus evolution of a typical lithium intercalation structure, as detailed below: First, a layered microstructure model is established; Then, the form of the stiffness matrix is given; Finally, the microstructure modulus is calculated.
[0012] Furthermore, a layered microstructure model was established, the specific process of which is as follows: During electrochemical processes, graphite exhibits a series of typical phase structures, including the initial interlayer graphite C, the fourth-order phase LiC, and so on. 36 3rd phase LiC 27 2nd phase LiC 12 The modulus information of the above five lithium intercalation structures was calculated using the first-order phase LiC6.
[0013] Furthermore, the form of the stiffness matrix is given, and the specific process is as follows: First, graphite and its lithium-intercalated structure are considered as transversely isotropic materials; Then, based on the crystal structure symmetry, its stiffness matrix is simplified to have 5 independent elastic coefficients. c 11 , c 12 , c 33 , c 44 and c 13 The form is represented as follows: (1) Furthermore, the microstructure modulus is calculated, and the specific process is as follows: First, under small strain conditions, the elastic energy of a solid can be expressed as: (2) in, V It is the unit cell volume before deformation, Δ E This refers to the energy change caused by strain. c ij The elastic coefficient, e i For strain components; Then, for a known structure, different types of strain are applied to it. d According to equation (2), its energy change Δ is obtained. E To obtain a series of Δ E and d The theoretical function expression, C (Δ E , d ); Finally, the energy and strain data calculated using DFT are fitted to obtain the elastic coefficients. c ij .
[0014] Furthermore, step C establishes an electrochemically induced stress characterization model based on microstructure strain and modulus, the specific process of which is as follows: First, combining step B, the electrochemically induced three-dimensional stress can be expressed as: (3) in s i , c ij , e i These represent the stress component, stiffness coefficient, and strain component, respectively. Then, combining with step A, for the microstructure deformation caused by lithium intercalation, shear deformation is generally ignored, and in-plane deformation is considered to be in an isobiaxial state, that is... e 1= e 2, e 4= e 5= e 6=0, adopted e in-plane Indicating in-plane strain e 1 and e 2. Adopt e out-plane Indicates interlayer strain e 3. The stress-strain relationship of the microstructure can be further expressed as: (4) Subsequently, the stress in the lithium-intercalated structure is reduced to only two equal in-plane stresses. s 1, s 2, and interlaminar stress s 3, same as above s in-plane Indicating in-plane stress s 1 and s 2, s out-plane Indicates interlayer stress s 3. Further simplification yields the following stress-strain relationship: (5) Finally, equation (5) is the constitutive relation of stress in electrochemically induced layered microstructures, where the elastic coefficients... c 11 , c 33 These are the in-plane modulus and interlaminar modulus, respectively, and the elastic modulus. c 12 , c 13 Equation (5) illustrates the functional relationship between microstructure stress, elastic coefficient, and microstructure strain, respectively, and solves the mechanical model problem of microstructure stress characterization.
[0015] The beneficial effects of this invention are as follows: This invention proposes a novel method for characterizing electrochemically induced microstructure stress based on experiments, simulations, and modeling. It considers key factors such as microstructure anisotropy, strain type, and modulus nonlinearity to ensure the accuracy of the mechanical description and achieve a comprehensive characterization of microstructure mechanics.
[0016] This invention integrates Raman spectroscopy and XRD to achieve in-situ comprehensive acquisition of three-dimensional strain in microstructures; it uses DFT to calculate the modulus changes of typical graphite lithium-intercalated structures under different lithium concentrations to obtain the in-plane and interlayer elastic coefficients and their variation with the amount of lithium intercalation; for transversely isotropic layered materials, it establishes a functional relationship model between electrochemically induced microstructure stress, strain, and elastic modulus, which can calculate in-plane stress and interlayer stress, and achieve quantitative characterization of three-dimensional stress evolution.
[0017] Based on the proposed microstructure stress characterization method, this invention can analyze the important role of graphite electrode microstructure mechanics in the lithium storage process. At the same time, this method can be further extended to other layered electrode materials and sodium and potassium storage systems, providing an important means for mechanical-electrochemical coupling analysis. Attached Figure Description
[0018] Figure 1 This is a schematic diagram representing the invention; Figure 2 This is a schematic diagram of the assembly structure of the graphite electrode in this invention; Figure 3 These are in-situ experimental curves of three-dimensional strain, namely interlaminar strain and in-plane strain, during the electrochemical process of this invention. Figure 4 This is a flowchart of the DFT calculation of the modulus of the graphite lithium-intercalated structural material in this invention; Figure 5 This is a schematic diagram of the layered microstructure in this invention; Figure 6 This is the evolution curve of the three-dimensional stress, namely interlayer stress and in-plane stress, of the graphite electrode microstructure during the electrochemical process of this invention. Detailed Implementation
[0019] The present invention will now be described in detail with reference to the accompanying drawings and embodiments: like Figure 1 As shown, the in-situ characterization method for the microstructure stress of graphite electrodes during electrochemical processes includes the following steps: A. In-situ measurement of three-dimensional strain evolution information of microstructures using spectral synthesis technology; B. The modulus evolution of typical lithium intercalation structures was calculated using DFT; C. Establish an electrochemically induced stress characterization model based on microstructure strain and modulus.
[0020] Step A includes in-situ experiments on the three-dimensional deformation of microstructures based on graphite electrodes, the specific process of which is as follows: First, composite electrodes are prepared using graphite materials; Then, using a graphite composite electrode as the positive electrode, metallic lithium as the negative electrode, and a 25µm thick microporous polypropylene membrane as the separator, the battery was assembled in a vacuum glove box. Its structural schematic diagram is shown below. Figure 2 As shown; Finally, to achieve in-situ measurement of deformation, a CR2032 button cell with a transparent window and a PI film was used for in-situ observation and signal acquisition of the electrochemical process.
[0021] The spectral synthesis technique in step A involves the following steps: First, Raman spectroscopy was used to measure the in-plane strain of the microstructure. Then, XRD was used to measure the interlayer strain of the microstructure.
[0022] The XRD method was used to measure the interlayer strain of microstructures, and the specific process is as follows: First, XRD instruments were used to collect spectral information in real time during the electrochemical process. By tracking the changes in the diffraction angle of the graphite diffraction peaks, the interlayer spacing parameters of the graphite lattice structure during the electrochemical process were given by Bragg's law. Then, based on the obtained interlayer spacing parameters, the specific expression of the micro-interlayer strain information of graphite is further calculated.
[0023] The specific process of measuring in-plane strain in microstructures using Raman spectroscopy is as follows: Raman spectroscopy was used to collect spectral information in real time during the electrochemical process, and the specific expression of strain information in the graphite microstructure was obtained by tracking the changes in 2D peak positions.
[0024] Step B uses DFT to calculate the modulus evolution of a typical lithium intercalation structure. The specific process is as follows: First, a layered microstructure model is established; Then, the form of the stiffness matrix is given; Finally, the microstructure modulus, i.e. the stiffness matrix, is calculated.
[0025] The specific process for establishing a layered microstructure model is as follows: During electrochemical processes, graphite exhibits a series of typical phase structures, including the initial interlayer graphite C, the fourth-order phase LiC, and so on. 36 3rd phase LiC 27 2nd phase LiC 12 The modulus information of the above five lithium intercalation structures was calculated using the first-order phase LiC6.
[0026] The form of the stiffness matrix is given, and the specific process is as follows: First, graphite and its lithium-intercalated structure are considered as transversely isotropic materials; Then, based on the crystal structure symmetry, its stiffness matrix is simplified to have 5 independent elastic coefficients. c 11 , c 12 , c 33 , c 44 and c 13 The form is represented as follows: (1) The specific process for calculating the microstructure modulus, i.e., the stiffness matrix, is as follows: First, under small strain conditions, the elastic energy of a solid can be expressed as: (2) in, V It is the unit cell volume before deformation, Δ E This refers to the energy change caused by strain. c ij The elastic coefficient, e i For strain components; Then, for a known structure, different types of strain are applied to it. d According to equation (2), its energy change Δ is obtained. E To obtain a series of Δ E and d The theoretical function expression, C (Δ E , d ); Finally, the energy and strain data calculated using DFT are fitted to obtain the elastic coefficients. c ij .
[0027] Step C establishes an electrochemically induced stress characterization model based on microstructure strain and modulus. The specific process is as follows: First, combining step B, the electrochemically induced three-dimensional stress can be expressed as: (3) in s i , c ij , e i These represent the stress component, stiffness coefficient, and strain component, respectively. Then, combining with step A, for the microstructure deformation caused by lithium intercalation, shear deformation is generally ignored, and in-plane deformation is considered to be in an isobiaxial state, that is... e 1= e2, e 4= e 5= e 6=0, adopted e in-plane Indicating in-plane strain e 1 and e 2. Adopt e out-plane Indicates interlayer strain e 3. The stress-strain relationship of the microstructure can be further expressed as: (4) Subsequently, the stress in the lithium-intercalated structure is reduced to only two equal in-plane stresses. s 1, s 2, and interlaminar stress s 3, same as above s in-plane Indicating in-plane stress s 1 and s 2, s out-plane Indicates interlayer stress s 3. Further simplification yields the following stress-strain relationship: (5) Finally, equation (5) is the constitutive relation of stress in electrochemically induced layered microstructures, where the elastic coefficients... c 11 , c 33 These are the in-plane modulus and interlaminar modulus, respectively, and the elastic modulus. c 12 , c 13 Equation (5) illustrates the functional relationship between microstructure stress, elastic coefficient, and microstructure strain, respectively, and solves the mechanical model problem of microstructure stress characterization.
[0028] Specifically, step A involves fabricating a composite electrode using graphite material, and the specific process is as follows: First, natural graphite, carbon black, and PVDF are ground in a mass ratio of 90:5:5 and then dissolved in NMP. Then, after thorough stirring, the uniform graphite slurry is coated onto the copper mesh current collector with a scraper. After vacuum drying at 120°C for 24 hours, it is punched into a circular electrode sheet with a diameter of 15mm.
[0029] Specifically, in step A, the electrolyte used in assembling the battery is a 1 M LiPF6 mixed solution of ethylene carbonate, methyl ethyl carbonate, and ethyl acetate in a volume ratio of 18:52:15.
[0030] Specifically, in step A, Raman spectroscopy is used to measure the in-plane strain of the microstructure, as follows: When a microstructure undergoes in-plane deformation, its lattice vibration frequencies (phonons) change and are reflected in the spectral peak positions. oh In terms of changes, tensile strain will cause the peak position to decrease, while compressive strain will cause the peak position to increase.
[0031] For graphite materials, the microstructural deformation caused by electrochemical processes is reflected in the changes in the peak positions of the Raman characteristic peaks G and 2D. Furthermore, the change in the 2D peak position is linearly correlated with the in-plane strain. Therefore, the in-plane strain of the microstructure can be obtained through the change in the 2D peak, expressed as: e =-Δ oh / (2 oh 0γ), where, oh 0 is the initial peak position. c It is the Greenerson parameter, Δ oh It's a change in peak position.
[0032] Specifically, in step A, XRD is used to measure the interlayer strain of the microstructure, as follows: When the optical path difference generated by the X-rays reflected from adjacent parallel crystal planes of the sampled object is equal to an integer multiple of the wavelength, X-ray diffraction will occur, and the diffraction direction and the interlayer spacing satisfy Bragg's law.
[0033] For graphite materials, the microstructural deformation caused by electrochemical processes alters the diffraction angles of the graphite peaks. Using Bragg's law, the interlayer spacing can be determined. d , is represented as: d = nλ / (2sin i ),in n It is a diffraction series. l It is the wavelength of X-rays. i It is the diffraction angle. Interlayer strain can be obtained further from the variation in interlayer spacing, expressed as: e =| d – d 0| / d 0. Among them d 0 represents the initial interlayer spacing.
[0034] Based on the above, a constant current charge-discharge experiment was conducted at room temperature using a LAND-CT2001A battery testing system (Wuhan) at a C / 7 rate between 1.5V and 0.01V. Simultaneously, in-situ spectral experiments were performed: Raman spectra were acquired using a Witec confocal Raman microscope with a 532 nm wavelength laser and a 50× telephoto lens. The laser power was controlled below 5mW, and the spot diameter was approximately 1 μm. Data was acquired every 10 minutes. X-ray acquisition was performed using a Smartlab diffractometer with a scanning angle range of 2... i The angle is between 20° and 30°, and the scanning rate is 10° / min.
[0035] Based on the spectral information obtained from two types of spectroscopic acquisitions during the electrochemical process, commercial software was used to fit the data and extract the corresponding characteristic peak information, thereby obtaining the evolution curve of the three-dimensional deformation of the microstructure during the electrochemical process, such as... Figure 3 As shown.
[0036] Material modulus of the graphite lithium intercalation structure (Li-GICs) in step B The modulus changes related to the electrochemical state of the graphite electrode microstructure were calculated using the DFT method. Its core consists of three steps: establishing a layered microstructure model, giving the form of the stiffness matrix, and calculating the microstructure modulus, i.e., the stiffness matrix. The flowchart is as follows: Figure 4 As shown.
[0037] b1. Layered microstructure model During electrochemical processes, graphite exhibits a series of typical phase structures, including the initial interlayer graphite C, the fourth-order phase LiC, and so on. 36 3rd phase LiC 27 2nd phase LiC 12 And the first-order phase LiC6. The modulus information of these five lithium-intercalation structures was mainly calculated. Table 1 shows their bond lengths and average interlayer spacing, and their corresponding layered microstructure diagrams are shown below. Figure 5 As shown.
[0038] .
[0039] b2. Stiffness matrix form of Li-GICs Since graphite and its lithium-intercalated structure can both be considered transversely isotropic materials, their stiffness matrix can be simplified to have 5 independent elastic coefficients based on the symmetry of their crystal structure. c 11 , c 12 , c 33 , c 44 and c 13The form is represented as follows: (1).
[0040] b3. Calculate the material modulus Under small strain conditions, the elastic energy of a solid can be expressed as: (2); in, V It is the unit cell volume before deformation, Δ E This refers to the energy change caused by strain. c ij The elastic coefficient, e i For strain components.
[0041] For a known structure, apply different types of strain. d According to equation (2), its energy change Δ is obtained. E To obtain a series of Δ E and d The theoretical function expression, C (Δ E , d The elastic coefficients are obtained by fitting the energy and strain data calculated using DFT. c ij .
[0042] Table 2 summarizes the calculated modulus (elastic modulus) of graphite and its typical lithium-intercalated structures. The results show that the interlayer modulus of the reaction layer increases with increasing lithium intercalation content. c 33 Significantly increased, intrasurface modulus of reaction c 11 Slightly decreased, and c 11 Compare c 33 It is much larger. In summary, DFT calculations provide modulus evolution information for typical lithium intercalation structures, offering important data support for microstructure stress characterization.
[0043] .
[0044] The electrochemically induced three-dimensional stress constitutive model for layered structures has been described above and will not be repeated here. Based on the above process, the microstructural stress evolution during the electrochemical process of the graphite electrode can be obtained, such as... Figure 6 As shown.
[0045] This invention achieves comprehensive characterization of the microstructure mechanics of graphite electrodes during electrochemical processes, providing a basis for revealing the electrode's micro-mechanical-electrochemical coupling behavior and lithium storage mechanism, as well as optimizing battery structure design. Specifically, it achieves the following functions: 1. It can realize in-situ experimental measurement of microscale in-plane strain and interlayer strain evolution in electrochemical processes; 2. It can characterize the material modulus related to lithium concentration in typical phase structures; 3. It can realize the quantitative characterization of in-plane stress and interlayer stress of microstructure in electrochemical processes.
[0046] This invention proposes a novel method for characterizing electrochemically induced microstructure stress based on experiments, simulations, and modeling. It considers key factors such as microstructure anisotropy, strain type, and modulus nonlinearity to ensure the accuracy of the mechanical description and achieve a comprehensive characterization of microstructure mechanics.
[0047] This invention integrates Raman spectroscopy and XRD to achieve in-situ comprehensive acquisition of three-dimensional strain in microstructures; it uses DFT to calculate the modulus changes of typical graphite lithium-intercalated structures under different lithium concentrations to obtain the in-plane and interlayer elastic coefficients and their variation with the amount of lithium intercalation; for transversely isotropic layered materials, it establishes a functional relationship model between electrochemically induced microstructure stress, strain, and elastic modulus, which can calculate in-plane stress and interlayer stress, and achieve quantitative characterization of three-dimensional stress evolution.
[0048] Based on the proposed microstructure stress characterization method, this invention can analyze the important role of graphite electrode microstructure mechanics in the lithium storage process. At the same time, this method can be further extended to other layered electrode materials and sodium and potassium storage systems, providing an important means for mechanical-electrochemical coupling analysis.
Claims
1. An in-situ characterization method for the microstructure stress of graphite electrodes during electrochemical processes, characterized in that: Includes the following steps: A. In-situ measurement of three-dimensional strain evolution information of microstructures using spectral synthesis technology; B. The modulus evolution of typical lithium intercalation structures was calculated using DFT; C. Establish an electrochemically induced stress characterization model based on microstructure strain and modulus.
2. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 1, characterized in that: Step A includes in-situ experiments on the three-dimensional deformation of microstructures based on graphite electrodes, the specific process of which is as follows: First, composite electrodes are prepared using graphite materials; Then, the battery was assembled in a vacuum glove box using a graphite composite electrode as the positive electrode, lithium metal as the negative electrode, and a 25µm thick microporous polypropylene membrane as the separator. Finally, to achieve in-situ measurement of deformation, a CR2032 button cell with a transparent window and a PI film was used for in-situ observation and signal acquisition of the electrochemical process.
3. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 1, characterized in that: The spectral synthesis technique in step A involves the following steps: First, Raman spectroscopy was used to measure the in-plane strain of the microstructure. Then, XRD was used to measure the interlayer strain of the microstructure.
4. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 3, characterized in that: The XRD method was used to measure the interlayer strain of microstructures, and the specific process is as follows: First, XRD instruments were used to collect spectral information in real time during the electrochemical process. By tracking the changes in the diffraction angle of the graphite diffraction peaks, the interlayer spacing parameters of the graphite lattice structure during the electrochemical process were given by Bragg's law. Then, based on the obtained interlayer spacing parameters, the specific expression of the micro-interlayer strain information of graphite is further calculated.
5. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 4, characterized in that: The specific process of measuring in-plane strain in microstructures using Raman spectroscopy is as follows: Raman spectroscopy was used to collect spectral information in real time during the electrochemical process, and the specific expression of strain information in the graphite microstructure was obtained by tracking the changes in 2D peak positions.
6. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 1, characterized in that: Step B uses DFT to calculate the modulus evolution of a typical lithium intercalation structure. The specific process is as follows: First, a layered microstructure model is established; Then, the form of the stiffness matrix is given; Finally, the microstructure modulus is calculated.
7. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 6, characterized in that: The layered microstructure model is established as follows: During electrochemical processes, graphite exhibits a series of typical phase structures, including the initial interlayer graphite C, the fourth-order phase LiC, and so on. 36 3rd phase LiC 27 2nd phase LiC 12 The modulus information of the above five lithium intercalation structures was calculated using the first-order phase LiC6.
8. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 7, characterized in that: The form of the stiffness matrix is given, and the specific process is as follows: First, graphite and its lithium-intercalated structure are considered as transversely isotropic materials; Then, based on the crystal structure symmetry, its stiffness matrix is simplified to have 5 independent elastic coefficients. c 11 , c 12 , c 33 , c 44 and c 13 The form is represented as follows: (1)。 9. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 8, characterized in that: The specific process for calculating the microstructure modulus is as follows: First, under small strain conditions, the elastic energy of a solid can be expressed as: (2); in, V It is the unit cell volume before deformation, Δ E The energy change caused by strain. c ij The elastic coefficient, ε i For strain components; Then, for a known structure, different types of strain are applied to it. δ According to equation (2), its energy change Δ is obtained. E To obtain a series of Δ E and δ The theoretical function expression, C (Δ E , δ ); Finally, the energy and strain data calculated using DFT are fitted to obtain the elastic coefficients. c ij .
10. The in-situ characterization method for the microstructure stress of graphite electrodes during the electrochemical process according to claim 1, characterized in that: Step C establishes an electrochemically induced stress characterization model based on microstructure strain and modulus. The specific process is as follows: First, combining step B, the electrochemically induced three-dimensional stress can be expressed as: (3); in σ i , c ij , ε i These represent the stress component, stiffness coefficient, and strain component, respectively. Then, combining with step A, for the microstructure deformation caused by lithium intercalation, shear deformation is generally ignored, and in-plane deformation is considered to be in an isobiaxial state, that is... ε 1 = ε 2, ε 4 = ε 5= ε 6=0, adopted ε in-plane Indicating in-plane strain ε 1 and ε 2. Adopt ε out-plane Indicates interlayer strain ε 3. The stress-strain relationship of the microstructure can be further expressed as: (4); Subsequently, the stress in the lithium-intercalated structure is reduced to only two equal in-plane stresses. σ 1, σ 2, and interlaminar stress σ 3, same as above σ in-plane Indicating in-plane stress σ 1 and σ 2, σ out-plane Indicates interlayer stress σ 3. Further simplification yields the following stress-strain relationship: (5); Finally, equation (5) is the constitutive relation of stress in electrochemically induced layered microstructures, where the elastic coefficients... c 11 , c 33 These are the in-plane modulus and interlaminar modulus, respectively, and the elastic modulus. c 12 , c 13 Equation (5) illustrates the functional relationship between microstructure stress, elastic coefficient, and microstructure strain, respectively, and solves the mechanical model problem of microstructure stress characterization.